Manual of Gynecardiology Female-Specific Cardiology - Maas, Angela H.E.M.; Bairey Merz, C. Noel.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a much-needed, internationally oriented text, focusing on specific aspects of heart disease in women. Despite the large amount of information available, there is still considerable confusion regarding female patients. As such, the book highlights the health events that occur during aging in women and that may influence the future CVD risk. For instance, pregnancy-related disorders are important predictors for CVD risk in women, and inflammatory diseases like rheumatic, thyroid disorders etc, which also interfere with CVD risk, are also more common in women. Adopting a multidisciplinary approach, including gynecology and endocrinology, it offers separate chapters on female-specific manifestations of ischemic heart disease, such as Tako Tsubo CMP and spontaneous coronary artery dissections. The book also discusses the effects and side effects of important medications. The chapters are clearly formatted, making it easy for readers to find subjects of interest.
Epidemiology cardiovascular disease in women -- Gender differences in traditional risk factors -- Female-specific risk factors -- Stable coronary artery disease -- Microvascular coronary artery disease -- Acute coronary syndromes -- Cardiovascular critical ill female patient -- Heart failure in women -- The female ECG and rhythm disorders -- Aortic diseases and peripheral arterial disease in women -- Stroke and cognition disorders in women -- Inflammatory disorders and CVD in women -- Gynecardiology in clinical practice -- Communication, coping with stress and psychosocial factors and CVD in women -- Pharmacotherapy in women.
Keywords: Medicine; Cardiology; Primary care (Medicine).; Medicine & Public Health; Cardiology; Primary Care Medicine